The role of the core capabilities dimensions in international business An analytical study in a sample of companies operating in the field of travel and aviation services in Dohuk Governorate - Gulli, Mehvan; Kochar, Jotiar (Humanities Journal of University of Zakho, 2020)
The present research is an attempt to define the mission of core competencies diemensions in orienting towards international business. Hence, for conducting the study practically, travel and aviation sectors have been identified due to this purpose. In order to decide the practical analysis of study, a hypothetical model was developed to show the relationship between the variables understudy, depending on (47) target field-tested companies specialized in travel and aviation in Dohuk Governorate. The research included (109) workers of the target companies. The data were collected by using a questionnaire accomplished for this purpose. The data were analyzed statistically by consulting the SPSS program (version 22), finding correlations and effects between the research variables.The research came to a number of conclusions. The most significant one is the presence of a positive correlation between core competencies diemensions and international business. Further, there exists a moral effect of core competences diemensions in international business, In the light of findings, some points were suggested. The most significant of which is the necessity of promoting and maintaining the availability of high levels of core competencies diemensions exploiting them to enhance the ability of going towards international business.